Optimized design and field experiment of a staggered vibrating subsoiler for conservation tillage - Wang, YunXia; Osman, Abdalla N; Zhang, Dongxing; Yang, Li; Cui, Tao; Zhong, Xiangjun (International Journal of Agricultural and Biological Engineering, 2019)
Soil compaction is a common problem facing conservation fields that restricts crop root growth and causes yield decrease. Subsoil techniques have been developed to break up the compaction layer. However, subsoil implement requires large draft power that hampered the development of subsoil techniques for most of developing countries due to lack of large scale tractors. Aiming to optimize the penetration resistance of the subsoiler and create a good working environment for the operators, a staggered vibrating subsoiler was developed. A new staggered vibrating mechanism was designed to generate the staggered vibration of the shanks meanwhile the V-shape shanks arrangement was adopted to keep relative balance for the subsoiler. In order to obtain optimum working parameters of the vibration frequency and forward speed, the trajectory of shanks was simulated by using the MATLAB software. The forward speed of 2-3 km/h with vibration frequency of 12 Hz was recommended to acquire an effective decrease in draft force. Field performance of this subsoiler was evaluated in terms of the draft force, power requirement and tractor wheel slippage. By comparing the two operation modes, staggered vibrating (SV) and rigid (NV) of shanks, the decrease ratios of draft force for SV were determined by 16.97%, 12.12% and 9.02% at forward speeds of 2.2 km/h, 2.6 km/h and 3.1 km/h, respectively. This is better than the research for the 1SZ-460 vibratory subsoiler that was decreased by 9.09% in draft force. The power requirement for SV was not significantly greater than that for NV. The obviously decreased wheel slippage was observed for SV by decrease of 12.47%, 17.96% and 21.79% at forward speeds of 2.2 km/h, 2.6 km/h and 3.1 km/h, respectively. In conclusion, the staggered vibrating subsoiler presents preferable working performance and is recommended to be applied in subsoil tillage process for developing countries. Keywords: vibrating subsoiler, staggered vibrating mechanism, V-shape arrangement, field experiment DOI: 10.25165/j.ijabe.20191201.4297 Citation: Wang Y X, Osman A N, Zhang D X, Yang L, Cui T, Zhong X J. Optimized design and field experiment of a staggered vibrating subsoiler for conservation tillage. Int J Agric & Biol Eng, 2019; 12(1): 59–65.